Maternal Paracetamol Intake During Pregnancy—Impacts on Offspring Reproductive Development - Tadokoro-Cuccaro, Rieko; Fisher, Benjamin G.; Thankamony, Ajay; Ong, Ken K.; Hughes, Ieuan A. (Frontiers in Toxicology, 2022)
Paracetamol (acetaminophen) is the preferred antipyretic/analgesic for pregnant women as it is believed there are no adverse fetal effects at the recommended dose. However, emerging evidence suggests that intrauterine paracetamol exposure may be associated with certain urogenital/reproductive disorders in the offspring. In this mini-review, we describe human fetal sex development and possible pharmacological mechanisms by which paracetamol may disrupt this process, including reduced testicular production of testosterone and/or insulin-like peptide 3. We then review the available epidemiological literature on associations between maternal paracetamol exposure and offspring sexual development. Three epidemiological studies have reported associations between maternal paracetamol intake and increased risk of cryptorchidism, although five others have not. None have found associations with hypospadias or penile length. Two out of three studies have reported a shorter anogenital distance (a marker of androgen action during the masculinisation programming window, ~8-14 weeks of gestation) in male infants antenatally exposed to paracetamol. One study has described a dose-dependent relationship between maternal paracetamol consumption and earlier female (but not male) attainment of puberty. Such epidemiological analyses are complicated by various factors, including method of paracetamol exposure assessment (usually retrospective self-report), variation in diagnostic accuracy, selection bias, confounding by clinical indication, and demographic/genetic differences between geographically separated populations. There is an urgent need for stronger evidence in this area, from both relevant experimental studies and large, carefully-designed prospective studies. In the meantime, a precautionary attitude to gestational paracetamol usage should be considered as the evidence for clinically significant reproductive effects in humans is limited.